2019
DOI: 10.1002/ncp.10394
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis Reduction Using an Exclusive Human‐Milk Diet and Probiotic Supplementation in Infants With 1000–1499 Gram Birth Weight

Abstract: Background Necrotizing enterocolitis (NEC) is a major complication confronting clinicians caring for premature infants. This investigation compares clinical outcomes before and after quality improvement–program interventions in a population of premature infants at intermediate risk for NEC. Methods This study is a retrospective single‐center chart review of infants admitted with a birth weight of 1000–1499 g, excluding major congenital anomalies, over a 6‐year period, beginning with implementation of a donor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… [7] In recent years, the rapid development of perinatal science and neonatal intensive care treatment technology have significantly improved the survival of low birth weight or premature infants. [8] Although the symptoms of NEC can be relieved through conservative treatments such as fasting, parenteral nutrition, fluid resuscitation, antibiotics, and maintaining acid-base balance, there are still a considerable number of children with NEC that require surgical treatment. [ 9 , 10 ] Therefore, it is necessary to further explore the clinical features and influencing factors of NEC in low birth weight infants, and provide evidence support for the prevention and treatment of clinical NEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [7] In recent years, the rapid development of perinatal science and neonatal intensive care treatment technology have significantly improved the survival of low birth weight or premature infants. [8] Although the symptoms of NEC can be relieved through conservative treatments such as fasting, parenteral nutrition, fluid resuscitation, antibiotics, and maintaining acid-base balance, there are still a considerable number of children with NEC that require surgical treatment. [ 9 , 10 ] Therefore, it is necessary to further explore the clinical features and influencing factors of NEC in low birth weight infants, and provide evidence support for the prevention and treatment of clinical NEC.…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and mortality are higher in premature infants with LBW or gestational age less than 36 weeks [7] . In recent years, the rapid development of perinatal science and neonatal intensive care treatment technology have significantly improved the survival of low birth weight or premature infants [8] . Although the symptoms of NEC can be relieved through conservative treatments such as fasting, parenteral nutrition, fluid resuscitation, antibiotics, and maintaining acid-base balance, there are still a considerable number of children with NEC that require surgical treatment [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…28,43 In addition, it is essential to inform parents that 63 RCTs, 30 observational studies and many meta-analyses including the Cochrane review have found probiotics to be safe in preterm (non-surgical) infants. [11][12][13][14][15]35,[50][51][52][53][54][55][56] Our pilot RCT 1 and the RCT by Powell et al 27 found probiotics to be safe in neonates with CGISC. The only published case report of mortality after probiotic supplementation in a preterm (non-surgical) infant was because of contamination of the product.…”
Section: Safety Of Probioticsmentioning
confidence: 63%
“…Probiotic supplementation is safe and beneficial even in extremely preterm infants without surgical conditions and reduces the risk of NEC, feed intolerance, and lateonset sepsis. [11][12][13][14][15] RANDOMISATION Since our pilot RCT 1 had a small sample size of 60 infants, we used computer-generated random sequence numbers in random blocks of two and four to ensure that an equal number of infants receive probiotics or a placebo. However, this method did not minimise the chance of unequal distribution of essential confounders (e.g.…”
Section: Sample Sizementioning
confidence: 99%
“…After reading the remaining 77 in detail, another 47 citations were excluded for various reasons (Figure 1). Meyer and Alexander 2017 (Lactoferrin) (24) and Sato et al (human milk fortifier) (25) were excluded as the cointerventions might have an effect on primary outcomes. Finally, 30 high-quality non-RCTs (n = 77,018; Probiotics: 21,008, Control: 56,010) from 18 countries were included in the systematic review .…”
Section: Resultsmentioning
confidence: 99%